On Relations between Creativity, Innovation, and Quality Management Culture in Europe as a Responce to Crisis and Post-crisis Period - Ceko, Enriko (European Scientific Journal, ESJ, 2023)
Purpose: Using regression analysis, the paper aims to clarify the relationship between innovation and creativity, innovation and quality management, and creativity and quality management. Design/methodology/approach – The paper opted for an exploratory study using regression analysis to find relations between innovation and creativity, innovation and quality management, and creativity and quality management, using data complemented Global Innovation Index and Creativity index and ISO 9001 standards certificate issued in European countries. Findings – The paper provides statistical insights about the relations between innovation and creativity, innovation and quality management, and creativity and quality management. It suggests that successful business organizations should invest in innovation, creativity, and quality management to achieve competitive advantage. Research limitations/implications – Because of the chosen research approach, the research results may need extended periods of investigation, therefore, researchers are encouraged to test the proposed propositions further. Practical implications – The paper includes implications for the development of a powerful tool combining innovation, creativity, and quality management, achieving a competitive advantage. Originality/value – This paper fulfills for the first time under a regression analysis an identified need to study how innovation, creativity, and quality management are related strongly between them. Practical / Industrial value: The outcome of the research stresses the value of investing in innovation, creativity, and quality management to achieve a competitive advantage, considering the importance of soft factors of production (entrepreneurship and innovation) as much important as hard factors of production (labor, land, and capital) too.